Melaka historical comic strip / Nursyahirah Abd Halim, Nordiana Tasha Mustiran and Filzah Haniz Mohamed Azman - Abd Halim, Nursyahirah; Mustiran, Nordiana Tasha; Mohamed Azman, Filzah Haniz (2017)
Interpretation acquired an importance growing process in delivering information. Interpretation design usually used for heritage interpretation (Tilden, 2007). Design interpretation usually help to shape visitor experience, ideas and information and encouraging visitor to seek information. Interpretation design will be more different and become more meaningful rather than just a props (Roberts, 2014). Interpretation design provides the primary interface between an organization and its visitors, design outcomes playing role in creating visitor experiences and communicating intended messages to the audiences (Woodward, 2009). Designers being likes to put on addition interpretive layer to an established visitors environment rather than contributing to the foundations of the visitor experience. In other words, enjoyment comes from a good match between visitor wants and what the destination offers. Comic is one of the preferred communication media and provides the principal reading access for million people (Negrete, 2013). Comics also are one of the attractive ways to convey information that include of narrative as well in graphical forms (Greenfield, 2000). Image and narrative can contribute to learning because they act as element in individual long term memory to people minds (Mcloud, 1993). Comic strips can be used to attract people to read story or a fact by using graphical than using long words. Roberts (2014) Interpretation in museum, zoos and heritage sites aims to inform, provoke and inspire the visiting public. Usually interpretation meaning is translation to an information. This can be proven by Coren (2013), interpretation is an important step in processing information in communication process. Interpretation is a special kind of communication that is particularly relevant to tourism and recreation (Knudson, 1995). An effective interpretation can contribute to a sustainable tourism that can give quality experience for visitors and good impact to the management of the visitors (Kotler, 1996). In the evolution of cartoon and comics, not all comics and cartoon are arts. Based on Einser (2008) cartoon is a narrative form that combines written text and graphical elements that have interrelated.